From Classroom to Chaos: The Early‐in‐Career Mental Health Nursing Experience. A Qualitative Descriptive Study - Louise Alexander; Gabrielle Burdeu; Anita Cappello; Keith Griffin (International Journal of Mental Health Nursing, 2026)
ABSTRACT Persistent challenges remain in attracting and retaining early‐in‐career mental health nurses in Australia. Key contributing factors include gaps in undergraduate nursing preparation, with many students reporting insufficient mental health placement experience to inform career choice. Health services have responded to recognised gaps between undergraduate preparation and the realities of clinical practice by developing structured early‐in‐career programs, such as graduate nurse and transition‐to‐practice initiatives. These programs combine supported clinical exposure, targeted education and mentorship to consolidate core skills. However, early‐in‐career mental health nursing practice often occurs within unpredictable and complex environments that can be hostile and emotionally demanding, compounding stress for recently graduated nurses. This study aimed to explore early‐in‐career mental health nurses' experiences of (1) workplace readiness, (2) wellbeing and (3) preparedness for practice. Using a qualitative descriptive design, we recruited 12 early‐in‐career mental health nurses from a tertiary hospital in metropolitan Melbourne, Australia. Semi‐structured interviews were thematically analysed according to Braun and Clarkes methodology. From analysis, four themes were identified: (1) Feeling ready, becoming ready; (2) Finding the right fit; (3) Practising under pressure; and (4) Organisational influences on readiness. This study provides important insights into early‐in‐career nursing experiences, highlighting the role of placement quality, exposure to workplace violence and organisational support in shaping preparedness and workforce retention. Variability in placement experiences contributed to misaligned expectations and heightened transition challenges. Findings also underscore occupational violence perpetrated by consumers and their family members highlighting the need for targeted preparation during undergraduate education and early career transition, as well as organisational responses to support safe workplaces.